2022
DOI: 10.1038/s41526-022-00228-1
|View full text |Cite
|
Sign up to set email alerts
|

Optic nerve sheath diameter and spaceflight: defining shortcomings and future directions

Abstract: Neuro-ocular changes during long-duration space flight are known as spaceflight-associated neuro-ocular syndrome (SANS). The ability to detect, monitor, and prevent SANS is a priority of current space medicine research efforts. Optic nerve sheath diameter (ONSD) measurement has been used both terrestrially and in microgravity as a proxy for measurements of elevated intracranial pressure. ONSD shows promise as a potential method of identifying and quantitating neuro-ocular changes during space flight. This revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…This would represent the inner diameter of the dura sheath (i.e., the diameter of the subarachnoid space) if the dura signal is considered hyperechoic 22,31 or the outer diameter of the dura sheath if the dura signal is considered hypoechoic. 32 Our average ONSD values (4.7 [0.5] mm horizontal and 5.1 [0.4] mm vertical for seated; 5.0 [0.6] mm horizontal and 5.3 [0.5] mm vertical for HDT) are consistent with the mean subarachnoid space diameter measured in the supine position using ultra-high field MRI (4.9 [0.5] mm horizontally and 5.2 [0.6] mm vertically). 26 The same MRI study reported a dura thickness (0.5 mm) similar to that from the post-mortem specimen, namely a 1 mm larger ONSD when dura thickness is included.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This would represent the inner diameter of the dura sheath (i.e., the diameter of the subarachnoid space) if the dura signal is considered hyperechoic 22,31 or the outer diameter of the dura sheath if the dura signal is considered hypoechoic. 32 Our average ONSD values (4.7 [0.5] mm horizontal and 5.1 [0.4] mm vertical for seated; 5.0 [0.6] mm horizontal and 5.3 [0.5] mm vertical for HDT) are consistent with the mean subarachnoid space diameter measured in the supine position using ultra-high field MRI (4.9 [0.5] mm horizontally and 5.2 [0.6] mm vertically). 26 The same MRI study reported a dura thickness (0.5 mm) similar to that from the post-mortem specimen, namely a 1 mm larger ONSD when dura thickness is included.…”
Section: Discussionmentioning
confidence: 99%
“…There are many inherent variabilities in ONSD, such as individual differences in the optic nerve and ONSDs, variable sheath dilatation in response to elevated ICP, 17 transient sheath diameter changes from eye movements 18,38 and constraints from instrument resolution. There are also modifiable variables such as B‐scan probe type and frequency, gain setting, scanning planes, measurement location and marker positions, body/head position, image quality control/artifacts and user experience 30,32,39 . Research does not show a consensus on the scanning plane.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6] Noninvasive ICP may be useful in low-resource settings, including wilderness enviroments, 7 combat settings, and spaceflight. 8 Limitations to widespread utilization of ONSD include suboptimal inter-and intra-observer reliability, 9,10 need for expert operators, 11,12 and large variability in methods used to perform measurements. 13,14 Automation using machine learning (ML) can address these limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasonographic optic nerve sheath diameter (ONSD) is a noninvasive ICP surrogate 3–6 . Noninvasive ICP may be useful in low‐resource settings, including wilderness enviroments, 7 combat settings, and spaceflight 8 . Limitations to widespread utilization of ONSD include suboptimal inter‐ and intra‐observer reliability, 9,10 need for expert operators, 11,12 and large variability in methods used to perform measurements 13,14 .…”
Section: Introductionmentioning
confidence: 99%